Innovative Ways of Integrating Public Health Into the Medical School Curriculum - McNeal, Meryl S. (2011)
This is one of six short papers that describe additional innovations to help integrate public health into medical education; these were featured in the “Patients and Populations: Public Health in Medical Education” conference. They represent relatively new endeavors or curricular components that had not been explored in prior publications. Although evaluation data are lacking, it was felt that sharing a description of the methods use by Morehouse School of Medicine to integrate public health in the curriculum would be of value to medical educators.